Fluoroquinolone-associated suspected tendonitis and tendon rupture: A pharmacovigilance analysis from 2016 to 2021 based on the FAERS database - Yamin Shu; Qilin Zhang; Xucheng He; Yanxin Liu; Pan Wu; Li Chen (Frontiers Media S.A., 2022)
Objective: The objective of this study was to scientifically and systematically explore the association between fluoroquinolones (ciprofloxacin, levofloxacin, and moxifloxacin) and tendonitis and tendon rupture through the Food and Drug Administration Adverse Event Reporting System (FAERS) database.Methods: Disproportionality analysis was used to quantify the signals of fluoroquinolone-associated suspected tendonitis and tendon rupture based on the FAERS data from January 2016 to March 2021. Clinical characteristics, the onset time, oral and intravenous administrations, and the serious outcomes of fluoroquinolone-associated tendonitis and tendon rupture were further analyzed.Results: Out of 35,667 fluoroquinolone-associated adverse events recorded in the FAERS database during the study period, 1,771 tendonitis and 1,018 tendon ruptures induced by fluoroquinolones as the suspected drug were analyzed, with a median age of 49.88-63.87 years. All three fluoroquinolones detected positive signals of tendonitis and tendon rupture in the four methods. Ciprofloxacin had the strongest statistical association with tendonitis with the highest positive signal values (ROR 98.50, PRR 93.25, IC 6.15, and EBGM 76.80), while levofloxacin showed the strongest statistical association with tendon rupture (ROR 76.38, PRR 73.75, IC 5.84, and EBGM 63.89). Compared with ciprofloxacin and levofloxacin, moxifloxacin was relatively weakly associated with tendonitis and tendon rupture. Oral fluoroquinolone-induced tendonitis and tendon rupture had a stronger signal strength than intravenous administration. The majority of fluroquinolone-related suspected tendonitis and tendon rupture tended to occur within a few days or one month. As for the disability rate of tendonitis, ciprofloxacin counted the highest (n = 461, 50.94%), with moxifloxacin the lowest (n = 20, 29.41%).Conclusion: Fluoroquinolone-induced tendonitis and tendon rupture tended to occur early and might result in serious outcomes. Our study provided valuable references for early identification of the risk of fluoroquinolone-induced tendonitis and tendon rupture.